Effect of pre-alloy composition on the content of ferromagnetic phase of MnBi melt spun ribbons - Nguyen, Truong Xuan; Nguyen, Ca Xuan; Nguyen, Tung Thanh; Nguyen, Vuong Van (Vietnam Journal of Science and Technology, 2020)
The rare-earth-free hard magnetic material MnBi is potential for permanent magnet high-temperature applications. The ferromagnetic phase (noted as a Low Temperature Phase – LTP) MnBi has the moderate spontaneous magnetization Ms 74 emu/g, the high magneto-crystalline energy Ka of 0.9 MJ/m3, and the elevated Curie temperature Tc 360 oC and especially, the positive thermal coefficient of coercivity d(iHc)/dT > 0. Up to now, the MnBi powders with high LTP content and coercivity have usually been prepared using the melt-spinning technique. However, the large difference in the melting temperature Tm of the two constituents, Mn and Bi, and the strong reactivity of Bi with the copper-based wheel make the preparation of high-performance MnBi ribbons difficult. Using a novel approach, we overcame these difficulties and prepared the MnBi ribbons on the conventional commercial melt-spinning furnace ZGK-1. The influences of pre-alloy compositions on the magnetic properties of MnBi melt – spun ribbons will be discussed in detail.